Regulatory Challenges in Supervising Digital Sharia Financial Product Innovation: Indonesia's Financial Services Authority After The Enactment of The P2SK Law - Setya Wahyu Ningrum; Mutiara Apriliyani; Ali Bakhrom (Faculty of Law, Muhammadiyah University of Surabaya, 2025)
This article analyzes the challenges faced by Indonesia’s Financial Services Authority (OJK) in supervising digital sharia financial product innovation following the enactment of the Law on Financial Sector Development and Strengthening (P2SK Law). The rapid expansion of digital sharia financial services, including fintech and digital banking, has generated complex regulatory issues concerning legal certainty, consumer protection, and compliance with sharia principles. This study employs a normative juridical method through the analysis of statutory regulations, OJK regulatory frameworks, and sharia governance mechanisms within Indonesia’s financial sector. The findings reveal that the P2SK Law has strengthened OJK’s supervisory mandate and provided a more comprehensive legal foundation for overseeing digital financial innovation. However, significant challenges persist in adapting regulatory frameworks to technological developments, ensuring effective sharia compliance, enhancing supervisory capacity, and strengthening institutional coordination among relevant stakeholders. These challenges may reduce the effectiveness of regulatory oversight and create legal uncertainty in the digital sharia finance ecosystem. The study concludes that an integrated, adaptive, and technology-oriented supervisory framework is essential to balance innovation, legal certainty, consumer protection, and adherence to sharia principles, thereby supporting the sustainable development of Indonesia’s digital sharia financial sector.